Facteurs d’adoption des foyers améliorés en milieux urbains sahéliens camerounais - Patrick Arnold Ombiono Kitoto (Développement Durable et Territoires)
In Cameroon Sahel, the combined effect of fuel-wood dependence and population growth has caused wide superiority of demand over supply. This imbalance is now causing a crisis for both environmental, economic and health. To reduce this demand and preserve the regional ecological equilibrium, improved stoves are offered by the state and various international organizations programs. But, their adoption is still low in both urban and rural areas. This study highlights the factors likely to reinforce the adoption in urban areas. The methodology uses data from a survey conducted in the city of Kousseri coupled with econometric analyzes based on the Heckman (1979) selection model and refined by Van De Ven and Van Praag (1981). Our results suggest that the action that seems relevant and likely to be an effective lever to the expansion of improved stoves is organizing awareness campaigns among men, heads of household. This must also be accompanied by the promotion of education, non-agricultural occupations.